2020
DOI: 10.1099/mgen.0.000409
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic approaches in microbial ecology: an update on whole-genome and marker gene sequencing analyses

Abstract: Metagenomics and marker gene approaches, coupled with high-throughput sequencing technologies, have revolutionized the field of microbial ecology. Metagenomics is a culture-independent method that allows the identification and characterization of organisms from all kinds of samples. Whole-genome shotgun sequencing analyses the total DNA of a chosen sample to determine the presence of micro-organisms from all domains of life and their genomic content. Importantly, the whole-genome shotgun sequencing approach re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
117
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(124 citation statements)
references
References 236 publications
(315 reference statements)
1
117
0
6
Order By: Relevance
“…In addition, ResistoXplorer supports other normalization methods like centered log-ratio (clr) and additive log-ratio (alr) transformation to facilitate compositional data analysis. The choice of method is dependent upon the type of analyses to be performed ( 20 , 31 ). The normalized data is used for exploratory data analysis including ordination, clustering and integrative analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, ResistoXplorer supports other normalization methods like centered log-ratio (clr) and additive log-ratio (alr) transformation to facilitate compositional data analysis. The choice of method is dependent upon the type of analyses to be performed ( 20 , 31 ). The normalized data is used for exploratory data analysis including ordination, clustering and integrative analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The best results are achieved from a trade-off between data characteristics (sample or group size, sequencing depth, effect sizes, genes abundances, etc.) and the normalization method, incorporated with the coupled exploratory and comparative analysis ( 31 ). Therefore, various statistical and normalization methods are required for different metagenomic datasets, analyses and research questions addressed ( 6 , 19 , 25 , 26 , 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ResistoXplorer supports other normalization methods like centered log-ratio (clr) and additive log-ratio (alr) transformation to facilitate compositional data analysis. The choice of method is dependent upon the type of analyses to be performed [20,31].…”
Section: Data Upload and Processingmentioning
confidence: 99%
“…[20,25,26,46]. Indeed, it has been recently suggested that metagenomic analysis should be explored comparatively using different available approaches [31]. However, this is a time consuming task and requires knowledge and bioinformatics training on the implementation of each statistical method employed.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation